Outcome of Conservative vs Surgical Management of Clavicle - Muhammad Zahid Iqbal, Waseem Ahmad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Clavicle fractures are common orthopedic injuries, particularly in young, active individuals. Management of midshaft clavicle fractures remains controversial, with options including conservative treatment and surgical fixation. While conservative care avoids surgical risks, displaced fractures may result in nonunion, malunion, and delayed functional recovery. Surgical fixation aims to restore anatomy, permit early mobilization, and improve functional outcomes. Evidence comparing both approaches in local populations remains limited. Objective: To compare the functional and radiological outcomes of conservative versus surgical management of clavicle fractures in adult patients. Methods: A prospective comparative observational study was conducted at Department of Orthopaedic Surgery, BBSTH/ DHQ Hospital Abbottabad from Sep 2022 to August 2023. Adult patients (18–60 years) with acute midshaft clavicle fractures were enrolled and allocated to conservative or surgical treatment groups. Conservative management involved arm sling immobilization and physiotherapy, while surgical patients underwent open reduction and internal fixation with precontoured plates. Functional outcomes were assessed using the Constant–Murley shoulder score at three and six months. Radiological outcomes included time to union, union rate, and incidence of nonunion. Complications were documented. Statistical analysis included t-tests and chi-square tests, with p < 0.05 considered significant. Results: A total of 120 patients were analyzed (62 conservative, 58 surgical). Surgical management resulted in significantly faster fracture union (11.2 ± 2.1 vs. 15.6 ± 3.4 weeks, p < 0.001), higher union rates (96.6% vs. 83.9%, p = 0.02), and superior Constant–Murley scores at six months (88.4 ± 6.2 vs. 78.1 ± 8.5, p < 0.001). Complications were fewer in the surgical group, although both approaches were generally safe. Conclusion: Surgical fixation of midshaft clavicle fractures provides faster union, higher union rates, and better early functional outcomes compared to conservative management, particularly in displaced fractures. Keywords: Clavicle fracture; Surgical fixation; Conservative treatment; Functional outcome